Effect of different levels of fat, sodium chloride, and sodium tripolyphosphate on the physicochemical and microstructure properties of Jamnapari goat meat emulsion modelling system - Ismail, Nur Aqilah; Bakar, Jamilah; Sazili, Awis Qurni; Mohammad Rashedi, Ismail Fitry (Universiti Putra Malaysia, 2021)
Jamnapari goat meat has the potential to be used for producing quality meat products. The present work thus aimed to evaluate the properties of Jamnapari meat emulsion. A two-level factorial design with three independent variables (23), fat (10 and 30%), sodium chloride (NaCl) (0.8 and 2.4%), and sodium tripolyphosphate (STPP) (0.5 and 1.5%) was used to randomly produce eight formulations of Jamnapari goat meat emulsion. The total expressible fluid (%TEF), expressible fat (%EFAT), pH, cooking loss, water holding capacity (WHC), texture, and microstructure properties of the eight Jamnapari goat meat emulsions were analysed. The %TEF was highly influenced by all factors (fat, NaCl, and STPP), while the